The Intention‐to‐Treat Effect of Bridging Treatments in the Setting of Milan Criteria–In Patients Waiting for Liver Transplantation. Issue 7 (20th June 2019) - Lai, Quirino; Vitale, Alessandro; Iesari, Samuele; Finkenstedt, Armin; Mennini, Gianluca; Onali, Simona; Hoppe‐Lotichius, Maria; Manzia, Tommaso M.; Nicolini, Daniele; Avolio, Alfonso W.; Mrzljak, Anna; Kocman, Branislav; et al.
Abstract : In patients with hepatocellular carcinoma (HCC) meeting the Milan criteria (MC), the benefit of locoregional therapies (LRTs) in the context of liver transplantation (LT) is still debated. Initial biases in the selection between treated and untreated patients have yielded conflicting reported results. The study aimed to identify, using a competing risk analysis, risk factors for HCC‐dependent LT failure, defined as pretransplant tumor‐related delisting or posttransplant recurrence. The study was registered atwww.clinicaltrials.gov (identification number NCT03723304). In order to offset the initial limitations of the investigated population, an inverse probability of treatment weighting (IPTW) analysis was used: 1083 MC‐in patients (no LRT = 182; LRT = 901) were balanced using 8 variables: age, sex, Model for End‐Stage Liver Disease (MELD) value, hepatitis C virus status, hepatitis B virus status, largest lesion diameter, number of nodules, and alpha‐fetoprotein (AFP). All the covariates were available at the first referral. After the IPTW, a pseudo‐population of 2019 patients listed for LT was analyzed, comparing 2 homogeneous groups of untreated (n = 1077) and LRT‐treated (n = 942) patients. Tumor progression after LRT was the most important independent risk factor for HCC‐dependent failure (subhazard ratio [SHR], 5.62; P  < 0.001). Other independent risk factors were major tumor diameter, AFP, MELD, patient age, male sex, and period of wait‐list registration. One single LRT was protective compared with no treatment (SHR, 0.51; P  < 0.001). The positive effect was still observed when 2‐3 treatments were performed (SHR, 0.66; P  = 0.02), but it was lost in the case of ≥4 LRTs (SHR, 0.80; P  = 0.27). In conclusion, for MC‐in patients, up to 3 LRTs are beneficial for success in intention‐to‐treat LT patients, with a 49% to 34% reduction in failure risk compared with untreated patients. This benefit is lost if more LRTs are required. A poor response to LRT is associated with a higher risk for HCC‐dependent transplant failure.